Setting Goals to Promote Academic and Personal Achievement - Eric D. Rubenstein; Andrew C. Thoron (EDIS)
Learners begin to envision their futures in both academic and personal settings even as children. The future that we develop motivates us to engage in learning environments, work experiences, and social encounters/settings. As instructors, we have the opportunity to help learners develop academic and personal goals that will develop and shape their future. This 3-page fact sheet assists instructors in developing their knowledge of goal theory, thereby allowing them to assist learners in utilizing their personal and academic goals to develop goal-directed achievement behaviors. Written by Eric D. Rubenstein and Andrew C. Thoron, and published by the UF Department of Agricultural Education and Communication, 2014.